Effect of undegradable dietary protein supplementation on early lactating crossbred dairy cows - K, Ally; A D, Mercy; T V, Vishwanathan (The Indian Journal of Animal Sciences, 2012)
A study was conducted for 100 days in crossbred dairy cows to assess the influence of degradability of dietary protein on milk production. Crossbred dairy cows (14) within 1 week of their lactation were selected and grouped into T1 and T2 as uniformly as possible. They were fed with isocaloric (72% TDN) and isonitrogenous (17% CP) concentrate mixtures with 2 levels of undegradable protein, i.e. 26.8 (T1) and 42.9 (T2) of the dietary CP. Paddy straw was the roughage fed and the ratio between concentrate and paddy straw was 70: 30 in the ration. The results showed no significant differences in the body weight of cows of the 2 groups. The dry matter intake and average daily milk yield of animals under T1 were higher than those of T2 from third and seventh weeks of the experiment, respectively. Percentage of milk fat and total solids and rumen ammonia nitrogen (mg/dl) were higher in T1. The cost of production of 1 kg milk was Rs 15.61 and 16.09, respectively, for the T1 and T2. It may be concluded that a concentrate mixture with a UDP level of 26.8% of CP improved the quality and quantity of milk in cows producing on an average 8–10 kg milk daily economically.